The Relationship Between Online Game Addiction And The Education Background Of Parents With The Interest Of Learning Islamic Religious Education In Students At Smk Muhammadiyah 2 Sleman - Kistoro, Hanif Cahyo Adi (TADRIS: Jurnal Pendidikan Islam, 2021)
This study aims to determine the relationship between online game addiction and parents' educational background with interest in learning Islamic religious education in students of SMK Muhammadiyah 2 Sleman. Religious education is the primary education that is mandatory for children. On the other hand, the current globalization in the world of technology, especially online games, which spreads among children and adolescents, is one of society's problems. The dependence on playing online games, one of the impacts is the existence of problems in psychological aspects, one of which is decreased interest in learning, especially in the field of Islamic education. Meanwhile, one of PAI education roles is as a filter to form a sound generation in people's lives. The problem phenomenon above becomes the problem formulation that will be studied in this study related to how the relationship between online games and the educational background of parents with interest in learning Islamic education in children of SMK Muhammadiyah 2 Sleman. There are two variables to be studied: the independent variable addiction to online games and parents' educational background. The dependent variable is the interest in learning Islamic education. The analysis technique used to determine the relationship between the variables of online game addiction and the parents' background with the student's PAI learning interest variable used the product-moment correlation technique with SPSS software version 23. Based on the results of data analysis, it can be seen that the significance is more than 0.05, namely 0.850. Meanwhile, according to r table, the value of 0.05 is 0.2787. This means that there is a relationship between student interest in learning and addiction to online games. The higher the addiction to online games, the lower the interest in learning PAI. The result of the relationship coefficient or r count is 0.028, indicating a small or weak contribution from online game addiction to interest in learning, namely 28 percent.